Should Dual Antiplatelet Therapy for Flow Diversion be Reduced to Monotherapy After 3 Months?. (16th November 2020) - Ban, Vin Shen; Pernik, Mark N; Binyamin, Tamar; Corona, Juan Mario; Kim, Young-Jun; de Oliveira Sillero, Rafael; Novakovic, Robin; Pride, G. Lee; Barr, John D; White, Jonathan A; Batjer, H. Huntington; Welch, Babu G
Abstract: INTRODUCTION: The flow diverter is a unique and important tool in the endovascular treatment of aneurysms. However, its use requires patients to be on dual antiplatelet therapy to prevent thromboembolic complications. The optimal duration of dual antiplatelet therapy is debated in light of its increased risk of hemorrhagic complications. METHODS: Patients undergoing flow diversion were prospectively enrolled in an institutional registry. Patients on dual antiplatelet therapy for <100 days were included in the short cohort while those on dual antiplatelet therapy for > = 100 days were included in the long cohort. The proportions of thromboembolic and hemorrhagic complications in these respective cohorts were compared using the Fisher's exact test. RESULTS: A total of 110 cases were eligible (mean age: 56.7 years). The majority were female (81.8%) and received the Pipeline Embolization Device (83.6%). 7.3% of patients presented with ruptured aneurysms. More than 1 flow diverter was required in 7.3% of cases. The majority (90.9%) of the dual antiplatelet regimen involved aspirin 325 mg and clopidogrel 75 mg. Most patients were on dual antiplatelet therapy between 3–6 months in duration prior to transitioning to aspirin monotherapy. In the shorter duration cohort, the thromboembolic complication rate was 9.3% compared to 12.5% in the longer duration cohort ( P  = .76). Similarly, the hemorrhagic complication rate was 5.6% in the short duration cohort compared to 14.3% in the longer duration cohort ( P  = .20). CONCLUSION: A shorter duration of dual antiplatelet therapy after flow diversion was not associated with a higher thromboembolic complication rate. While the duration of antiplatelet therapy should be personalized for each patient, transitioning to monotherapy after 3 months is likely safe.